Indonesia's Economic Foreign Policy Towards Thailand on Cross-Border Payment - Maharani, Rizka (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2025)
The payment digitalisation leads to financial integration with the cross-border payment implemented by ASEAN. This implementation is being conducted bilaterally among ASEAN member states, for instance between Indonesia, Malaysia and Thailand. The Memorandum of Understanding (MoU) signed by each central bank since 2022 aims to reduce the US dollar dependency which shows positive and progressive results. This issue is interesting to be studied further as the transaction of rupiah to ringgit is higher compared to baht, but Indonesia conducted the implementation of cross-border payment using QR Code for the first time with Thailand. Furthermore, there is a currency rate conversion between Indonesia and Thailand from each central bank. This article uses qualitative research methods with qualitative and quantitative data usage. Using the foreign economic policy which refers to Hiscox (2014), this article found that Indonesia has been cooperating with Thailand in using QR Code due to the exchange rate agreement between IDR and THB to maintain the stability of the exchange rates of each currency, people movement to travel that showed an increment in QR Code transactions, to perceive the mutual gains and recovery for the tourism and SMEs sectors, and private sector and independent central back involvement within this implementation. Keywords: Cross-border payment; Indonesia; QR Code; Thailand